A comparison between pure active pharmaceutical ingredients and therapeutic deep eutectic solvents: solubility and permeability studies - Duarte, Ana Rita C. (2017)
THEDES, so called therapeutic deep eutectic solvents are here defined as a mixture of two components, which at a particular molar composition become liquid at room temperature and in which one of them is an active pharmaceutical ingredient (API). In this work, THEDES based on menthol complexed with three different APIs, ibuprofen (ibu), BA (BA) and phenylacetic acid (PA), were prepared. The interactions between the components that constitute the THEDES were studied by NMR, confirming that the eutectic system is formed by H-bonds between menthol and the API. The mobility of the THEDES components was studied by PFGSE NMR spectroscopy. It was determined that the self-diffusion of the species followed the same behavior as observed previously for ionic liquids, in which the components migrate via jumping between voids in the suprastructure created by punctual thermal fluctuations. The solubility and permeability of the systems in an isotonic solution was evaluated and a comparison with the pure APIs was established through diffusion and permeability studies carried out in a Franz cell. The solubility of the APIs when in the THEDES system can be improved up to 12 fold, namely for the system containing ibu. Furthermore, for this system the permeability was calculated to be 14 105 cm/s representing a 3 fold increase in comparison with the pure API. With the exception of the systems containing PA an increase in the solubility, coupled with an increase in permeability was observed. In this work, we hence demonstrate the efficiency of THEDES as a new formulation for the enhancement of the bioavailability of APIs by changing the physical state of the molecules from a solid dosage to a liquid system.